Host plant shifts and transitions into new adaptive zones in leafhoppers: the example of Macropsinae (Homoptera: Auchenorrhyncha: Cicadellidae) of Russia and adjacent countries - Tishechkin, Dmitri Yu. (Zootaxa, 2016)
The modes of diversification of Palaearctic Macropsinae (Homoptera: Auchenorrhyncha: Cicadellidae) are reconstructed based on data on their host plants and distribution in Russia and the adjacent territories. Macropsinae (Homoptera: Auchenorrhyncha: Cicadellidae) is originally an Oriental group, which penetrated into the Palaearctic from Southeast Asia. The genus Pediopsoides and species of the genus Macropsis that feed on East Asian oaks have not dispersed beyond broadleaf forests of the Eastern Palaearctic. Apparently, Pediopsis and elm-feeding species of Macropsis initially dispersed throughout the entire broadleaf forest zone. Division of this zone into two widely separated parts in temperate areas of Europe and East Asia (nemoral disjunction), produced closely related vicariant pairs of sister species. The genus Oncopsis and species of Macropsis feeding on Salicaceae dispersed throughout the entire Palaearctic following their host plants. Both lineages penetrated into riparian forests of the foothills and midlands of Central Asia, where they produced endemic species. The Central Asian Macropsis lineage shifted from Salicaceae to trees and shrubs of unrelated families (wild roses, barberry, oleaster, and sea-buckthorn) growing in the same biotopes. Subsequent diversification on those plants produced several separate host-associated species-groups, some of which penetrated following their hosts from riparian forests into arid habitats. One such lineage apparently shifted from shrubs to wormwood species (Artemisia spp.) and thus gave rise to the genus Macropsidius. This genus underwent adaptive radiation on wormwood species in the plains of South Kazakhstan and Central Asia; advancing westward, it formed secondary centres of diversity in Transcaucasia and the Mediterranean. Finally, some lineage of Macropsidius (or its sister-group) switched from feeding on Artemisia to polyphagy, yielding the ancestral form of the genus Hephathus. In general, the evolution of the Macropsis–Macropsidius–Hephathus lineage in the Palaearctic closely followed the classical Simpsonian model: the group underwent diversification within a particular adaptive zone, then one lineage entered a new adaptive zone and secondarily diversified there, etc. Transitions into new adaptive zones by different Macropsinae lineages were probably caused by one of two factors: shift to a new plant unrelated to the original host (e.g., from Salicaceae to plants of other families) or adaptation to new microclimatic conditions (penetration from riparian forests into open arid habitats).